Ureaplasma septic polyarthritis in a young woman with neuromyelitis optica receiving rituximab. Issue 2 (1st February 2021) - Harold, Rachel; Simon, Gary L; Akselrod, Hana; Siegel, Marc O; Roberts, Afsoon
Abstract : We report a case of septic polyarthritis caused by Ureaplasma urealyticum in a woman with neuromyelitis optica who was receiving rituximab. Her case exemplifies some of the unique characteristics of invasive Ureaplasma infections that can lead to delayed diagnosis as well as treatment challenges including recurrence following antibiotic discontinuation.